Lithium and ECT: concurrent use still demands attention$dthree case reports - Sartorius, Alexander; Wolf, Joachim; Henn, Fritz A. (The world journal of biological psychiatry, 2009)
Bipolar disorders as well as recurrent major depressive episodes can be most effectively treated with electroconvulsive therapy (ECT). Since continuation/maintenance ECT is not well established, prophylactic therapy in recurrent illnesses is more commonly carried out using antidepressive medication alone or more often in combination with lithium. In case of relapse the clinically important question of discontinuation of lithium versus the concurrent use of ECT and lithium may arise. The safety of concurrent use has also to be balanced when lithium treatment is started within an ECT course. Since recent studies have reported no negative interactions with concurrent use, we here report three cases (one case of a prolonged seizure, a serotonin syndrome and a focal seizure) of severe lithium-induced side effects while patients underwent ECT without complications and lithium serum levels were still subtherapeutic. Clinical consequences are discussed and disturbances of the blood-brain barrier system as a speculative cause are hypothesized taking previous studies, animal studies and an additional reported clinical case into account.